A randomized controlled trial of very early rehabilitation in speech after stroke. Issue 5 (July 2016) - Godecke, Erin; Armstrong, Elizabeth A; Rai, Tapan; Middleton, Sandy; Ciccone, Natalie; Whitworth, Anne; Rose, Miranda; Holland, Audrey; Ellery, Fiona; Hankey, Graeme J; Cadilhac, Dominique A; Bernhardt, Julie
Rationale: The efficacy of rehabilitation therapy for aphasia caused by stroke is uncertain. Aims and hypothesis: The Very Early Rehabilitation of Speech (VERSE) trial aims to determine if intensive prescribed aphasia therapy (VERSE) is more effective and cost saving than non-prescribed, intensive (usual care-plus) and non-intensive usual care (UC) therapy when started within 15 days of stroke onset and continued daily over four weeks. We hypothesize that aphasia therapy when started very early after stroke and delivered daily could enhance recovery of communication compared with UC. Sample size estimates: A total of 246 participants (82 per arm) will provide 80% power to detect a 4.4% improvement on aphasia quotient between VERSE and UC plus at a significance level of α = 0.05. Setting: Acute-care hospitals and accompanying rehabilitation services throughout Australia, 2014–2017. Design: Three-arm, prospective, randomized, parallel group, open-label, blinded endpoint assessment (PROBE) trial. Participants: Acute stroke in previous 14 days and aphasia diagnosed by aphasia quotient (AQ) of the Western Aphasia Battery (WAB). Randomization: Computer-generated blocked randomization procedure stratified by aphasia severity according to Western Aphasia Battery, to one of three arms. Intervention: All participants receive UC—usual ward-based aphasia therapy. Arm 1: UC—no additional therapy; Arm 2 : UC-plus usual ward-based therapy; Arm 3: VERSE therapy—a prescribed and structured aphasia therapy program. Arms 2 and 3 receive a total of 20 additional sessions (45–60 min, provided daily) of aphasia therapy. The additional intervention must be provided before day 50 post stroke. Study outcome measures: The aphasia quotient of Western Aphasia Battery at 12 weeks post stroke. Secondary outcomes include discourse measures, the Stroke and Aphasia Quality of Life Scale-39 and the Aphasia Depression Rating Scale at 12 and 26 weeks. Economic evaluation: Incremental cost-effectiveness ratios at 26 weeks will be reported. Discussion: This trial is designed to test whether the intensive and prescribed VERSE intervention is effective in promoting maximum recovery and preventing costly health complications in a vulnerable population of survivors of stroke. It will also provide novel, prospective, aphasia specific cost-effectiveness data to guide future policy development for this population.